Mobility segregation throughout the lifetime of highly segregated lower social profile inhabitants in Warsaw – case study - Grzegorczyk, Anna (Rozwój Regionalny i Polityka Regionalna, 2024)
The aim of the article is to define the concept of mobility segregation during lifetime and to distinguish mobility segregation scope among two Warsaw (Poland) inhabitants characterised by lower social profile, who lived in homogeneous social environment. Mobility has become a new dimension of social inequality that should be taken into account in research on social segregation in increasingly polarised cities. It can be studied by qualitative methods that can contribute to quantitative-dominant research on segregation. In this paper, mobility segregation aspects are analysed through biographic interviews, using reconstructive-interpretative approach. It gives a novel method to study segregation during lifetime in a holistic approach and to give evidence of experienced segregation of individual inhabitants. The study revealed that mobility segregation may change throughout the lifetime. There were indicated “windows of change” when forms and ranges of mobility change resulting in the change of places regularly visited and social profile of people met there. However these relations are complex.